Angiotensin II stimulates phosphorylation of high-molecular-mass cytosolic phospholipase A2 in vascular smooth-muscle cells. - Rao, G N (1994)
Phospholipase A2 (PLA2) may be one of the major components involved in cell signalling and proliferation, as suggested by recent studies. In this paper we show that the potent vasoconstrictor and hypertrophic agent angiotensin II (AngII) activates cytosolic PLA2 (cPLA2) in vascular smooth-muscle cells. AngII induced a rapid time-dependent release of [3H]arachidonic acid from prelabelled cells that was inhibited by mepacrine, a PLA2 inhibitor. AngII treatment of intact cells also activated a cPLA2, as measured in cell-free extracts by the release of radiolabelled arachidonic acid from exogenously added 1-stearoyl-2-[1-14C]arachidonoyl phosphatidylcholine. This AngII-stimulated cPLA2 activity was also significantly inhibited by mepacrine. AngII induced a rapid and time-dependent increase in cPLA2 phosphorylation. Protein kinase C (PKC) depletion inhibited both AngII-induced [3H]arachidonic acid release and cPLA2 phosphorylation. Together, these results suggest strongly that (1) AngII phosphorylates and activates cPLA2 in a PKC-dependent manner, and that (2) cPLA2 mediates the AngII-induced [3H]arachidonic acid release in vascular smooth-muscle cells.